(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Ilizarov systems are required to treat critical bone defects. However, they are not customized to the patient present significant risk of infection and induces pain and discomfort. This paper presents a novel customizable functional brace overcoming the main limitations of the Ilizarov system. This brace is being designed, together with clinicians, to be produced using additive manufacturing (AM). This paper presents preliminary design concept assessed using Finite Element Analysis (FEA), considering different impact loading conditions and different materials.